Analysis of Tumpang Sari Horticulture Farming in Pattappang Village, Gowa Regency - Fitri Anugrah Sari; Muh Ilmi Ikhsan Sabur; Siti Nurazizah Jufri; Ainim Paradita; Bima Wicaksana Pawiloi (Journal La Lifesci, 2020)
This research was prepared aiming to determine the amount of cost, income, and efficiency of vegetable farming in the Buluballea Environment, Pattappang Village, Tinggimoncong District, Gowa Regency. Besides this research is also to determine the effect of factors such as land area, labor, manure, urea fertilizer, KCl fertilizer, ZA fertilizer, and cropping patterns on costs and income. Tumpangsari Farming is planting in almost the same time for the same two types of crops. The basic method used in this research is descriptive study and is done by interview technique. The selection of sample farmers uses a stratified random sampling method with a total of 5 (five) people. The type of data used in the study is primary data and secondary data collected by interview, note-taking, and observation techniques